Effective microorganisms as halal-based sources for biofertilizer production and some socio-economic insights: a review - Yap, Chee Kong; Al Mutairi, Khalid Awadh (Multidisciplinary Digital Publishing Institute (MDPI), 2023)
This paper aims to review the literature on ‘Effective Microorganism (EM)’ and ‘Fertilizer’ from the Scopus database and to discuss EMs using Halal-based sources for biofertilizer production from socio economic insights. Based on EM and fertilizer publications on the Scopus database, all the 17 papers reviewed provided no detailed information on the Halal-status of the biofertilizers inoculated with EM. The impacts of Halal-certified biofertilizers will trigger the Halal certification in food products by (a) catering for the increasing Halal food demand due to expectedly Muslim population expansion, (b) contributing to the sustainable buying behaviour of Halal products’ consumers in the future, (c) catering for the increasing number of Muslim travellers around the world, (d) becoming a positive driver for higher production of more Halal foods that can enhance food safety, human health and well-being, and (e) creating a cost-effective and increasing food marketability. The later three points (c, d and e) play a very important role in a country’s societal well-being and economic growth and development. Although Halal-status is not a must for the world’s food marketing, Halal-certified biofertilizer for the Halal-status of food carries the greatest potential to enter the ever-expanding Muslim markets. Finally, it is postulated that the successful usage of EM using Halal-based sources for biofertilizer production will result in two major outcomes from the points of United Nations’ Sustainable Development Goals # 9 (Industry, Innovation and Infrastructure) and # 12 (Responsible Consumption and Production). Hence, the presented review provides a starting point for future research considering sustainability and innovation as priorities.